EPIDEMIOLOGY OF MENINGOCOCCAL INFECTION IN UZBEKISTAN AT THE PRESENT STAGE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Meningococcal disease (MD) is a serious public health care problem in most countries of the world, which is related to a high mortality and disability rate of people who have had this disease. The decline in the incidence of MD in the interepidemic period, which lasts more than 30 years in Uzbekistan, has led to a decrease the alertness of medical workers regarding this infection. Late diagnosis and hospitalization are often the reasons for untimely medical care.The analyse of the the age and sex structure of morbidity in meningococcal infection, serogroup landscape of the pathogen, clinical forms of meningococcal infection at the present stage was given in this article.